Comparing the gross motor performance levels of 7-10 age group children with autism spectrum disorder and typical developing - Ebubekir Aksay (IP Iermakov S.S., 2022)
Background and Study Aim. The children and adolescents with Autism Spectrum Disorder lead a sedentary lifestyle and, as a result, they are more affected by health problems such as being overweight and obese.  They are physically less active than their peers showing typical developing. The aim of the study is to carry out a general comparison of the gross motor performance levels of elementary school-age children living in Germany diagnosed with autism spectrum disorder and children showing typical developing. Material and Methods. A total of 68 children diagnosed with autism spectrum disorder and 73 children showing normal development between the ages 7 and 10 participated in the study. Of the participants, 55 were diagnosed with autism spectrum disorder were boys and 13 were girls, and the average age of the boys was 8.40±1.09 years, while the average age of the girls was 8.85±1.14 years. Of the 73 participants, 36 showing typical development consisted of boys and 37 of them consisted of girl students, and the average age of the boys was 8.56±1.08 years while the average age of the girls was 8.43±1.21 years. The Body Coordination Test for Children was used to evaluate gross motor performance components in the study. Results. The results of the study showed that girls had lower general body coordination than boys on average. It was concluded that children who had an autism spectrum disorder diagnosis displayed statistically lower total motor performance in all of the administered tests compared to their peers showing normal development (p<0.05). Conclusion. It is considered that the data obtained will provide important clues about the motor coordination values and body composition of children with autism spectrum disorder and will contribute to taking precautions against the health risks of children with autism spectrum disorder, who are more affected by a sedentary lifestyle compared to their normally developing peers.